Fundamentals of Entrepreneurship (ENT 300) : Juice and smoothies bar / Muhammad Azizan Suhaimi … [et al.] - Suhaimi, Muhammad Azizan; Mohamad, Izzat Muqri; Saipol, Mohamad Shafiq Shariz (2017)
This business is based on our discussion where we choose to open juice and smoothies bar instead of two (2) other business that is travel agencies and homestay. The business capital is around RM 100,000 to RM300,000 and its included our shop lot, renovation and raw material for making juice. Our juice bar is a company which focuses on juice production in Samarahan area. Juice is a healthy drink that contain many vitamins. The difference colour of the juice and smoothies drink makes it look interesting and suitable to serve for any occasion. Our juice also serves with ice that had been blend to make it more satisfaction for our customer because customer nowadays like to drink a cold drink. We are highly confident that our juice bar will easily developed because of the simple steps and ingredient that we used to make the juice.